Charcoal and Wood Vinegar Products from Hedge Bamboo by Using 200 Liters Community Charcoal Kiln Working with Gasified Biomass Burner - Kaewluan, Sommas; Sriromreun, Paranee; Narrat Jansri, Surachai; Asadamongkon, Pichai; Chuichulcherm, Sinsupha (Community and Social Development Journal, 2021)
The objective of the research was aimed to qualify and quantity the carbonization products from bamboo wood using new-design self-assembled kiln. The kiln comprised of a 200 liters cylindrical cabinet with an inlet heat source from a burner, an outlet for vapors passing through a condenser and a non-condensable gas burner. Heat source was 1000 °C oxygen-lean gas from a solid fuel burner, while the pyroligneous acid or “wood vinegar” was recovered in a condensing unit using tap water as a coolant at a flowrate of 4 liter per minute. The leftover, non-condensable gas was burn in a gas burner as a co-fuel and to reduce gas emission. Raw material was bamboo chunk chopped into a length of 7.5 cm and dried to abstain moisture contents of 27.78, 20.57 and 13.33% respectively. Three sets of experiment were conducted with altering bamboo moisture contents. The wood vinegar was collected every 5-minute intervals until no more wood vinegar was detected. The results show that using a 27.78% moisture content bamboo chunk, the carbonization process completed after 350 minutes, with mass yields of 22.38% charcoal and 59.25% wood vinegar were obtained. However, yield of charcoal increased when bamboo moisture content decreased, contrariety to wood vinegar. The quality of the carbonization products obtained from this work were well represented according to Thai community product standard. The production of bamboo charcoal and wood vinegar using this kiln can generate income for farmers up to 1,729 baht per run.